Ethnobotany: Ethnopharmacology to Bioactive Compounds - Book Review - Indah Sari, Anggi Mei (Ethnobotany Research and Applications, 2025)
Ethnobotany: Ethnopharmacology to Bioactive Compounds, edited by José L. Martinez, Alfred Maroyi and Marcelo L. Wagner. Routlege. London, UK, 2023, pp 246, GBP £124.00 (Hardback), GBP £42.39 (paperback), GBP £42.39 (eBook), ISBN 9781032348148 (hardback), ISBN 9781032348155 (paperback), ISBN 9781003323969 (eBook). As highlighted in Ethnobotany: Ethnopharmacology to Bioactive Compounds, edited by José L. Martinez, Alfred Maroyi, and Marcelo L. Wagner (2023), this book the examines the use of plants in traditional medicine, with an emphasis on the bioactive compounds found in medicinal plants. This study explored the potential of medicinal plants as sources of bioactive compounds for drug development. Several chapters have focused on the use of traditional plants that demonstrate biological activities related to the treatment of various diseases in humans and animals. This book serves as a significant reference in the fields of ethnobotany and pharmacology, offering insights into how traditional knowledge can support the development of new pharmaceuticals through ethnobotanical and pharmacological research.